Estimulación adecuada en la educación inclusiva - Cando Calapiña, Roció del Carmen (2016)
Children with cerebral palsy is a disorder that affects the central nervous system that is produced before, during and after childbirth so these children are abandoned by their parents for the disabled who have through this research project se realize exercises for children with cerebral palsy who aims to prepare a diagnosis of Adequate Stimulation in inclusive education "CASA ESPERANZA" in the neighborhood of the Parish Illuchi Belisario Quevedo. The methodology that was used was quantitative and qualitative because thanks to the contributions showed us through instruments such as the observation sheet for children and interview aimed at people who work in the home I can focus on and analyze the difficulties they had each child to carry out activities and in turn was the need to get help from professionals who are responsible for diagnosing problems with from the moment of birth are those in the perinatal, prenatal stages, postnatal for proper development cognitive, motor, language and emotional partner, concluded we realized that the institution must have government support for children to receive a better development: the growth of infants turn four areas that are developed to help the socialization of each of them and that people responsible take care of them are prepared to give a better future for everyone and are dependent and can implement is why schools have and should provide the same conditions, rights and obligations to receive children with special disabilities, and to develop in a better way, and that may be included in the public and private sectors.